2020
DOI: 10.1097/scs.0000000000006057
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Position of the Mandibular Foramen in Relation to the Dentoalveolar Plane in Pierre Robin Patients: Establishing Safety of the Horizontal Osteotomy

Abstract: Background: Mandibular distraction with horizontal osteotomy of the ramus and vertical distraction vector has successfully treated airway obstruction in young Pierre Robin patients. Placing the osteotomy just above the dentoalveolar plane can minimize damage to the inferior alveolar nerve. This study maps the position of the mandibular foramen relative to the height of the dentoalveolar plane to demonstrate the safety of this technique in Pierre Robin neonates. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…These discrepancies highlight the need for specific anatomic data given the edentulous, smaller, and micrognathic mandible in the very young Pierre Robin patient. The first part of our study identified the mandibular foramen as existing an average of 4.7 mm below the dentoalveolar plane 37 . An osteotomy above this intraorally visible and palpable landmark would, therefore, avoid nerve transection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These discrepancies highlight the need for specific anatomic data given the edentulous, smaller, and micrognathic mandible in the very young Pierre Robin patient. The first part of our study identified the mandibular foramen as existing an average of 4.7 mm below the dentoalveolar plane 37 . An osteotomy above this intraorally visible and palpable landmark would, therefore, avoid nerve transection.…”
Section: Discussionmentioning
confidence: 93%
“…The first part of our study identified the mandibular foramen as existing an average of 4.7 mm below the dentoalveolar plane. 37 An osteotomy above this intraorally visible and palpable landmark would, therefore, avoid nerve transection. It should be noted that the included study population in the CT component was small given that availability of both the requisite CT data and software package to allow for fine measurement was not available at the Children's Hospital Wisconsin until after 2011.…”
Section: Discussionmentioning
confidence: 99%
“…3,26,27 To evaluate safety with the mandibular osteotomies, small series have examined neonatal mandibular anatomy in patients with Pierre Robin sequence. 28,29 Virtual surgical planning has also become a useful tool for some to allow the design of custom osteotomy patterns to avoid collateral damage. 6,30 We identified seven osteotomy techniques that have been described for use in mandibular distraction osteogenesis.…”
Section: Safety Of Mandibular Osteotomies In Infants Withmentioning
confidence: 99%